2011
DOI: 10.1016/j.molcel.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Generates an Auto-Amplification Loop by Triggering the βTrCP- and CK1α-Dependent Degradation of DEPTOR

Abstract: DEPTOR is a recently identified inhibitor of the mTOR kinase that is highly regulated at the posttranslational level. In response to mitogens, we found that DEPTOR was rapidly phosphorylated on three serines in a conserved degron, facilitating binding and ubiquitylation by the F-box protein βTrCP, with consequent proteasomal degradation of DEPTOR. Phosphorylation of the βTrCP degron in DEPTOR is executed by CK1α, after a priming phosphorylation event mediated by either the mTORC1 or mTORC2 complexes. Blocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
222
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(232 citation statements)
references
References 28 publications
8
222
0
1
Order By: Relevance
“…Recent mechanistic studies identified CK1␣, S6 kinase 1, and RSK1 as other kinases that contribute to the degradation of deptor (51)(52)(53). Furthermore, deptor contains multiple phosphorylation sites for mTOR (TORC1 and TORC2) in a serine-rich domain between the second DEP and C-terminal PDZ domains (26, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Recent mechanistic studies identified CK1␣, S6 kinase 1, and RSK1 as other kinases that contribute to the degradation of deptor (51)(52)(53). Furthermore, deptor contains multiple phosphorylation sites for mTOR (TORC1 and TORC2) in a serine-rich domain between the second DEP and C-terminal PDZ domains (26, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Although the regulation of DEPTOR is complicated, it appears to be a natural inhibitor of both mTOR complexes because in its absence, S6K, AKT, and SGK activity increases (Peterson et al 2009). DEPTOR levels are controlled though the ubiquitin-dependent degradation pathway by a mechanism requiring direct phosphorylation of DEPTOR by mTOR in an apparent positive feedback loop (Peterson et al 2009;Duan et al 2011;Gao et al 2011;. Interestingly, DEPTOR levels are low in many cancers, which may promote mTOR-dependent cell growth, proliferation, and survival (Peterson et al 2009).…”
Section: The Mtor Complexes and Their Regulationmentioning
confidence: 99%
“…For example, DEPTOR, a negative regulator of MTOR signaling is ubiquitinated by SCF (BTRC/bTrCP) and degraded when MTOR activity is high. [7][8][9] Possibly the dephosphorylation of many cellular proteins upon MTOR inhibition enhances their susceptibility to ubiquitination and degradation, and such a mechanism has been reported for the regulator for growth factor signaling GRB10. 10,11 However, among the 4 proteins we found that show enhanced degradation upon MTOR inhibition, only SUPT6H is reported to be a putative substrate of MTOR, 10 and the increase in overall proteasomal degradation does not require CUL/cullin-based ubiquitin ligases, 6 which typically ubiquitinate phosphorylated proteins.…”
mentioning
confidence: 96%